Plants as populations of release sites for seed dispersal: a structural‐statistical analysis of the effects of competition on Raphanus raphanistrum. (6th June 2013) - Kelly, Natalie; Cousens, Roger D.; Taghizadeh, Mohammad S.; Hanan, Jim S.; Mouillot, David; Santamaria, Luis
<x xml:space="preserve">Abstract</x> The effect of competition on plant size is primarily a result of a reduction in initiation of branches. For species with limited dispersal ability, this results in a greatly modified seed shadow at short distances. In the case of agricultural weeds, the concentration of fruits at greater heights when competing with a crop might result in a greater proportion being dispersed long distances by harvesting machinery, but they would be fewer in number. <boxed-text content-type="graphic" id="jec12097-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>